Developing Control System of Electrical Devices with Operational Expense Prediction - Siti Sendari; Heru Wahyu Herwanto; Yuni Rahmawati; Dendi Mukti Putranto; Shofiana Fitri (IAES Indonesia Section, 2016)
The purpose of this research is to develop a system that can monitor and record home electrical device’s electricity usage. This system has an ability to control electrical devices in distance and predict the operational expense. The system was developed using micro-controllers and WiFi modules connected to PC server. The communication between modules is arranged by server via WiFi. Beside of reading home electrical devices electricity usage, the unique point of the proposed-system is the ability of micro-controllers to send electricity data to server for recording the usage of electrical devices. The testing of this research was done by Black-box method to test the functionality of system. Testing system run well with 0% error.